2003
DOI: 10.1128/iai.71.11.6270-6278.2003
|View full text |Cite
|
Sign up to set email alerts
|

DNA Immunization with the Gene Encoding P4 Nuclease ofLeishmania amazonensisProtects Mice against Cutaneous Leishmaniasis

Abstract: Infection with the protozoan parasite Leishmania amazonensis can cause diverse clinical forms of leishmaniasis. Immunization with purified P4 nuclease protein has been shown to elicit a protective response in mice challenged with L. amazonensis and L. pifanoi. To explore the potential of a DNA-based vaccine, we tested the L. amazonensis gene encoding P4 nuclease as well as adjuvant constructs encoding murine interleukin-12 (IL-12) and L. amazonensis HSP70. Susceptible BALB/c mice were immunized with the DNA en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 62 publications
1
45
0
1
Order By: Relevance
“…Previous studies have demonstrated the efficacy of parenteral DNA vaccines against murine leishmaniasis (4,12,28,34,39), but this is the first study to report the efficacy of a mucosal DNA vaccine for this disease. Altogether, the work presented here demonstrates the feasibility of using the nasal mucosa for effective delivery of both crude antigens and DNA against cutaneous leishmaniasis.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated the efficacy of parenteral DNA vaccines against murine leishmaniasis (4,12,28,34,39), but this is the first study to report the efficacy of a mucosal DNA vaccine for this disease. Altogether, the work presented here demonstrates the feasibility of using the nasal mucosa for effective delivery of both crude antigens and DNA against cutaneous leishmaniasis.…”
Section: Discussionmentioning
confidence: 94%
“…An alternative vaccination approach has been to immunize mice with DNA, where the protein product is produced in vivo from the plasmid DNA. This approach has been used successfully against both protozoan (7,16,29) and helminth (10,46,53,54) infections resulting in measurable immune responses, some of which mediate protective immunity.…”
mentioning
confidence: 99%
“…For example, a DNA vaccine encoding the highly conserved LACK antigen cannot induce cross-species protection (16,29), whereas L. donovani promastigote antigen dp72 can induce protection against both L. donovani and L. major in mice (43). A DNA vaccine encoding L. amazonensis P4 nuclease can also protect significantly against L. amazonensis and L. major, but different adjuvants (interleukin-12-or HSP70-encoding plasmids) are required to obtain such protection (8).…”
mentioning
confidence: 99%